IT Governance Maturity Assessment of the BRAVO Application Using an Integrated COBIT 2019 and ITIL 4 Framework - Zahra Diva Putri Munaspin; Dwi Rosa Indah; Habi Baturohmah; Ali Ibrahim; M. Rudi Sanjaya; M. Husni Syahbani (JUSIFO : Jurnal Sistem Informasi, 2025)
This study evaluates the maturity of IT governance supporting the BRAVO (BPKB Registration Vehicle Online) application at the Traffic Directorate of the South Sumatra Regional Police, a law enforcement institution delivering digital public services. An integrated evaluation approach combining COBIT 2019 and ITIL V4 frameworks was employed to assess governance and service management practices. Using design factor analysis, RACI-based respondent mapping, maturity level assessment, and gap analysis, the study focused on three key governance objectives: MEA03 (Managed Compliance with External Requirements), DSS02 (Managed Service Requests and Incidents), and DSS03 (Managed Problems). The findings indicate that MEA03 and DSS02 have achieved Maturity Level 3, reflecting structured and consistently implemented processes, while DSS03 remains at Maturity Level 2, indicating limited institutionalization of problem management practices. The gap analysis reveals significant maturity gaps between current and targeted levels, highlighting the need for governance strengthening, improved documentation, and enhanced analytical use of service data. This study demonstrates that integrating COBIT 2019 and ITIL V4 provides a coherent framework for bridging IT governance and service management, offering practical insights for improving digital public service delivery in law enforcement and other public sector organizations.